Antifungal, anti-yeast, anti-oxidant and HPLC analysis of different solvent extracted samples from Calamus aromaticus leaves (Bangladesh Journal of Pharmacology, 2015)
The antifungal, anti-yeast and anti-oxidant effects of Calamus aromaticus leaves were studied. The extract showed mild activity against two fungal strains and strong activity against the yeast. The results also indicated the presence of extremely high DPPH radical scavenging potential in all tested samples at each of the seven concentrations used. The data further revealed that ethyl acetate and n-butanol extracted samples measured highest antifungal (25.0% inhibition each against Rhizopus oryzae at 1000 µg/well), anti-yeast (73.5 and 66.4% activity respectively at 2000 µg/disc) and anti-oxidant (96.6 and 97.7% activity respectively at 250 ppm) potential while samples extracted with water were least potent. HPLC analysis of the extracted samples confirmed ethyl acetate and n-butanol as the solvents of choice for the extraction of antifungal, anti-yeast and anti-oxidant compounds (phenolics) from the leaves of C. aromaticus.